Effects of functional electrical stimulation-leg cycling exercise plus progressive resistance training on lower limb muscle strength and volume among individuals with chronic incomplete spinal cord injury / Nurhaida Rosley - Rosley, Nurhaida (2018)
Spinal cord injury is a catastrophic event which leads to significant disabilities and change in an individual’s lifestyle. It limits the ability to accomplish daily physical activities and engage in exercise, as well as the use of exercise equipment due to paralysis and environmental barriers. It has been widely established that exercise can improve the quality of life in individuals with SCI. One prominent method is the use of functional electrical stimulation-leg cycling exercise. To gain greater effects of exercise on the individual with SCI, it is recommended that they need to include resistance training. Thus, this study aimed to examine the effect of FES-LCE plus PRT on muscle strength and muscle volume among incomplete SCI. In this quasi-experimental study, 21 individuals with incomplete SCI were assigned into Control group and Intervention group (11 controls, 10 interventions) using purposive sampling. Intervention group received FES-LCE+PRT, while Control group received FES-LCE only. There were significant increased of isometric muscle peak torque on right and left quadriceps muscles, right and left hamstrings muscles, and left gastrocnemius muscles (P <0.001) after 12 weeks training. In addition, for lower limb muscle volumes there were a significant increased in both right and left lower limbs. There was also significant good correlation in left hamstring muscle peak torque and muscle volume in 6 weeks (r= 0.65, p = 0.03) and 12 weeks (r= 0.67, p= 0.04). However, muscle strength and muscle volume shown no different between group. Therefore, training with FES-LCE plus PRT had no effect on muscle strength and muscle volume among individuals with incomplete SCI.